2006
DOI: 10.1007/s00436-006-0236-6
|View full text |Cite
|
Sign up to set email alerts
|

Cell invasion by Trypanosoma cruzi amastigotes of distinct infectivities: studies on signaling pathways

Abstract: Trypanosoma cruzi metacyclic trypomastigotes of the major phylogenetic lineages use specific signaling pathways to invade host cells. Using a panel of drugs, we studied if the differences in the ability of extracellular amastigotes (EA) from G (T. cruzi I) and CL (T. cruzi II) strains to invade host cells could be associated to activation of specific signaling routes. Sonicated extracts from G or CL strain EA induced transient raises in HeLa cell intracellular Ca(2+) levels in a dose-dependent manner. Treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 43 publications
(74 reference statements)
1
23
0
4
Order By: Relevance
“…Although we observed a colocalization between amastigotes and Lucifer Yellow, this colocalization was more pronounced when we used trypomastigote. Many studies showed that, although capable of infecting a wide range of host cells, the mechanisms used by amastigotes may be different from those used by trypomastigotes, including molecules on the surface of host cell important for interaction, and protein kinase involved in the remodeling of the host cell cytoskeleton [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Although we observed a colocalization between amastigotes and Lucifer Yellow, this colocalization was more pronounced when we used trypomastigote. Many studies showed that, although capable of infecting a wide range of host cells, the mechanisms used by amastigotes may be different from those used by trypomastigotes, including molecules on the surface of host cell important for interaction, and protein kinase involved in the remodeling of the host cell cytoskeleton [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been reported that acidocalcisome Ca 2+ has a role in host cell invasion. Depletion of acidocalcisome Ca 2+ by pretreatment of invasive stages of T. cruzi with ionomycin plus nigericin or ionomycin plus NH 4 Cl, inhibited invasion of host cells (Fernandes et al, 2006; Neira et al, 2002). In T gondii , knockout of TgA1, the enzyme necessary for pumping Ca 2+ into the organelle results in de-regulation of cytosolic calcium, altered microneme secretion, and decreased virulence (Luo et al, 2004).…”
Section: Acidocalcisomes In Protistsmentioning
confidence: 99%
“…In other studies with T. cruzi I and II strains, metacyclic trypomastigotes from T. cruzi II were more infective than were those from T. cruzi I 33 . Conversely, FERNANDES et al 20 , using extracellular amastigotes of the same strains, demonstrated that T. cruzi I displayed much higher infectivity than T. cruzi II. Metacyclic trypomastigotes and amastigotes from these lineages depend on different signaling mechanisms to invade various types of host cells 19,20,33 .…”
Section: Discussionmentioning
confidence: 99%